Review of weather and climate forecast-based advisory frameworks for rice-based systems - Mabilangan, Abigail; Saito, Kazuki (International Rice Research Institute, 2025)
This report reviews weather and climate forecast-based advisory tools for rice-based agriculture, including WeRise, ORYZA, Climate+, PRiSM, PRiME, PICSA, PRISE, and IRAS. Each tool provides science-based, actionable recommendations to help users anticipate and manage risks associated with climate variability and extreme weather events. The report evaluates their architectures, core algorithms, required weather inputs, and integration potential into AgWise. The findings support a modular, risk-aware, and evidence-driven approach to generating advisories that can be applied not only in rice systems but also adapted for other crops and farming contexts.